Total Quality Management for Competitive Advantage in the UAE - Alneyadi, Amal (European Journal of Business and Strategic Management, 2023)
Purpose: The study purposed to examine the influence of total quality management on the competitive advantage of businesses in the United Arab Emirates. TQM has been studied in the past but not in the context of competitive advantage, especially in business in the United Arab Emirates. The paper aimed to examine TQM practices and their influence on businesses' competitive advantage in the United Arab Emirates. Methodology: The study utilized a quantitative method aligned with a positivist philosophy and a deductive approach. A structured questionnaire was used to glean data from 54 participants. The sample was chosen through random sampling. The questionnaire was launched online and withdrawn after the allocated timeline was depleted. The response rate was 90% at the time of the withdrawal. Data were analyzed using descriptive statistics. Findings: The results showed that different TQM practices such as customer focus, effective communication, continual improvement, fact-based decision making, strategic and systematic approach, integrated system, employee involvement, and process approach increased the business's competitive advantage in the United Arab Emirates. Also, the results showed that businesses that adopt TQM practices get time-based, cost, first mover, product differentiation, and price advantages through increasing customer satisfaction, reducing costs and defects, customer attraction, product quality loyalty, and product differentiation. Lastly, the result showed that TQM positively affects UAE business by increasing overall competitiveness. Unique Contribution to Theory, Practice and Policy: The study was anchored on customer focus theory which focuses on the customer, the modern market has arguably embraced this in the business environment where information systems development is considered. The findings of this study are insightful to business managers as they underpin the importance of implementing different TQM practices and leveraging them for competitive advantage